2007
DOI: 10.2217/17435889.2.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Multifunctional Magnetic Nanoparticles

Abstract: Magnetic nanoparticles and their magnetofluorescent analogues have become important tools for in vivo imaging using magnetic resonance imaging and fluorescent optical methods. A number of monodisperse magnetic nanoparticle preparations have been developed over the last decade for angiogenesis imaging, cancer staging, tracking of immune cells (monocyte/macrophage, T cells) and for molecular and cellular targeting. Phage display and data mining have enabled the procurement of novel tissue- or receptor-specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(135 citation statements)
references
References 98 publications
(108 reference statements)
0
134
0
1
Order By: Relevance
“…Mahmoudi et al have shown that at the same iron concentrations (above 2.25 mM), SPIONs with different surface coatings are toxic to human brain cells while completely compatible with human kidney cells. Cancer imaging • Utilized in clinical imaging of liver and spleen tumors and metastases through RES-mediated uptake • Effective in identification of lymph node metastases, useful in treatment of prostate, breast, and colon cancer • Prolonged delineation of brain tumor boundaries and quantify tumor volumes • Useful in imaging CNS tumor neovasculature and assessing therapeutic response to antiangiogenic chemotherapeutic agents 62,82,[191][192][193][194][195][196][197] Autoimmune disorders imaging • Used to visualize macrophage infiltration in brain, assess blood-brain barrier damage and neurological impairment in chronic relapsing experimental autoimmune encephalomyelitis, rodent model of human multiple sclerosis • Used to monitor distinct pattern of macrophage migration in acute disseminated encephalomyelitis 82,192,198,199 Central nervous system disease imaging • Serve as useful tool for noninvasive anatomic and temporal tracking of stem cells in CNS trauma and stroke • Used to monitor disease progression in epilepsy • Allows MRI visualization of neuroinflammation in vivo • Allows monitoring of leukocyte trafficking in the brain…”
Section: Excretionmentioning
confidence: 99%
“…Mahmoudi et al have shown that at the same iron concentrations (above 2.25 mM), SPIONs with different surface coatings are toxic to human brain cells while completely compatible with human kidney cells. Cancer imaging • Utilized in clinical imaging of liver and spleen tumors and metastases through RES-mediated uptake • Effective in identification of lymph node metastases, useful in treatment of prostate, breast, and colon cancer • Prolonged delineation of brain tumor boundaries and quantify tumor volumes • Useful in imaging CNS tumor neovasculature and assessing therapeutic response to antiangiogenic chemotherapeutic agents 62,82,[191][192][193][194][195][196][197] Autoimmune disorders imaging • Used to visualize macrophage infiltration in brain, assess blood-brain barrier damage and neurological impairment in chronic relapsing experimental autoimmune encephalomyelitis, rodent model of human multiple sclerosis • Used to monitor distinct pattern of macrophage migration in acute disseminated encephalomyelitis 82,192,198,199 Central nervous system disease imaging • Serve as useful tool for noninvasive anatomic and temporal tracking of stem cells in CNS trauma and stroke • Used to monitor disease progression in epilepsy • Allows MRI visualization of neuroinflammation in vivo • Allows monitoring of leukocyte trafficking in the brain…”
Section: Excretionmentioning
confidence: 99%
“…[4][5][6][7] The addition of bioactive molecules, such as adding targeting-moieties to the MNP surface, is employed to increase their specificity toward cellular targets, thus preventing their interaction with healthy tissue. [8][9][10] In recent years, cell labeling with MNPs has become a widely used method for several in vitro 11 and in vivo [1][2][3] applications, ranging from cell sorting to magnetic resonance imaging (MRI) tracking. 13 Furthermore, MNP-labeled cells that are transplanted in living rats can be manipulated in order to alter biodistribution and enable their accumulation in the intended target organ.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] A new emerging class of nanomaterials known as QDs are brightly fluorescent, enabling their use as imaging probes in both in-vitro and invivo systems, viz, molecular, cellular, and in-vivo imaging, tumor targeting, lymph node imaging, surface receptor targeting, and labeling. [8][9][10][11][12][13][14][15][16][17] QDs can be coupled with biomolecules such as antibodies, peptides, carbohydrates, and small molecules to target early stage malignant tumors for imaging and diagnosis.…”
Section: Introductionmentioning
confidence: 99%